The role of a high school one-to-one laptop initiative in supporting content area literacy, new literacies, and critical literacy - McKeeman, Leah Ann (Kansas State University, 2008)
The purpose of this study was to explore participants' (teachers, students, administrators, and parents) experiences and perceptions regarding the perceived impact a rural high school's one-to-one laptop initiative had on content area literacy, new literacy's, and critical literacy. Through a case study, data were collected through multiple sources and viewpoints to obtain an in-depth perspective of how this rural high school's one-to-one laptop initiative had perceivably impacted teacher's instruction to enhance student learning. Data were collected and analyzed through a blending of direct interpretation and categorical analysis, presenting the following findings. The one-to-one laptop initiative's technology was utilized: (a) by student participants for academic purposes, personal efficiency, and recreational purposes, (b) by teacher participants for educational purposes, and (c) within content area instruction. Resulting from the access to laptop technology, this study documented the purposes of finding information for assignments, facilitating "just in time" learning, and stimulating schema about curricular content. Content area literacy instruction was perceivably effected because of the multiple textual formats the technology provided, and instructional occurrences were documented as developing vocabulary and fostering either content comprehension or reading comprehension. The new literacy's and how they were implemented within the mathematics, language arts, science, and social studies classrooms were discussed. The role of critical literacy was presented in relation to students' sense of agency, and the power dynamic within various content area classes. The majority of participants were documented having a positive perception regarding the one-to-one laptop initiative. Although integration of technology was occurring, there were opportunities lacking that could further develop teachers' instruction to enhance student learning. When considering professional development within schools implementing a one-to-one technology initiative, administrative teams should: (a) consider what will be requisite versus elective technology integration tasks, and (b) ensure professional support is provided to teachers regarding integrating technology within their pedagogical practices. Additionally, teachers should instructionally integrate the technology tools and literacy's that students currently employ. Pedagogically, this study implies that teachers must expand their comfort zones regarding content area literacy, new literacy's, and critical literacy.
Keywords: new literacy's; content area literacy; critical literacy; one-to-one laptop initiative; secondary education; technology; Education, Reading (0535); Education, Secondary (0533); Education, Technology (0710)